1992
DOI: 10.1002/bip.360320812
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous volume transitions in ionic gels and their possible involvement in the nerve excitation process

Abstract: Discontinuous volume changes in polymer gels carrying negatively ionized groups were studied by varying the molarities of univalent and bivalent cations in the bathing solution. These studies offer a sound basis for elucidating the origin of rapid swelling and heat production in nerve fibers associated with the process of excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Interestingly, at the same molar ratios of divalent to monovalent cations, ~ 1 mM to 30 mM, respectively, similar volume changes were observed in biological polyelectrolyte systems during physiological processes like nerve excitation, musle contraction, and cell locomotion [34][35][36][37][38][39][40].…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Interestingly, at the same molar ratios of divalent to monovalent cations, ~ 1 mM to 30 mM, respectively, similar volume changes were observed in biological polyelectrolyte systems during physiological processes like nerve excitation, musle contraction, and cell locomotion [34][35][36][37][38][39][40].…”
mentioning
confidence: 52%
“…Interestingly, at the same molar ratios of divalent to monovalent cations, ~ 1 mM to 30 mM, respectively, similar volume changes were observed in biological polyelectrolyte systems during physiological processes like nerve excitation, musle contraction, and cell locomotion [34][35][36][37][38][39][40].Surfactants. The extensive theoretical [41][42][43] and experimental [44][45][46][47][48] studies have shown that addition of anionic, cationic, and nonionic surfactants to the solution containing a gel can also influence the volume phase transition temperature and swelling degree of hydrogels depending on their hydrophobicity and charge of the polymer network.…”
mentioning
confidence: 54%
“…At a critical concentration, a threshold is passed and the gel abruptly contracts. Data adapted from Tasaki and Byrne (1992) The second possibility is that described by Bray and Duke (2004) as Conformational Spread. They report the evidence that from a number of systems, for example, actin filaments and others, conformational changes can propagate through extended lattices of protein molecules.…”
Section: Gels and Phase Transition Cooperativity: Conformational Spreadmentioning
confidence: 99%
“…Again, the pioneer in exploring volume phase transitions of polyelectrolytes in the context of nerve excitation was Ichigi Tasaki (Tasaki and Byrne [67,68]; Tasaki [64,65]). He also measured the liberation of heat at wave onset both in action potentials and retinal spreading depressions (Tasaki and Iwasa [70]; Tasaki and Byrne [66]) phenomena that we now associate with relaxation of structured interfacial water involved in the polyelectrolyte response to changes induced by electrical and/or mechanical stimulation.…”
Section: The Basement Membrane and Extracellular Matrix As Charged Gementioning
confidence: 99%